Perceiving Etruscan Art: AI and Visual Perception - Maurizio Forte (Humans)
This research project is aimed at exploring the cognitive and emotional processes involved in perceiving Etruscan artifacts. The case study is the Sarcophagus of the Spouses at the National Etruscan Museum in Rome, one of the most important masterpieces in pre-Roman art. The study utilized AI and eye-tracking technology to analyze how viewers engaged with the Etruscan Sarcophagus of the Spouses, revealing key patterns of visual attention and engagement. OpenAI, ChatGPT-4 (accessed on 12 October 2024) was used in conjunction with Colab–Python in order to elaborate all the spreadsheets and data arising from the eye-tracking recording. The results showed that viewers primarily focused on the central figures, especially on their faces and hands, indicating a high level of interest in the human elements of the artifact. The longer fixation duration on these features suggest that viewers find them particularly engaging, which is likely due to their detailed craftsmanship and symbolic significance. The eye-tracking data also highlighted specific gaze patterns, such as diagonal scanning across the sarcophagus, which reflects the composition’s ability to guide viewer attention strategically. The results indicate that viewer focus centers on human elements, especially on faces and hands, suggesting that these features hold both esthetic and symbolic significance.